Effect of state level rabies control policy and terrestrial mammal reservoir on canine and feline rabies cases in the United States - Engelman, Leslie (My University, 2014)
Rabies is a fatal, encephalitic disease caused by numerous variants of a lyssavirus to which all mammals are susceptible. In the United States, domestic animal rabies prevention and control is subjective to individual state health departments; leading to a wide variety of control policies. This study was conducted to determine whether a correlation could be found between state rabies control policy and the incidence of rabies in canines and felines from 2009 through 2012. In addition, since several terrestrial mammal rabies reservoirs are native to different states throughout the country, an evaluation of relationship between prevalent terrestrial mammal rabies reservoir and the number of rabies positive cases was performed. States were grouped into regions based on the predominant rabies reservoir within state lines to determine if any correlation exists between the number of positive rabies cases in canines and felines and the terrestrial mammal reservoir. A state by state examination of domestic animal rabies control policy was conducted and positive rabies case data for canines and felines from 2009 through 2012 were obtained by contact with state public health representatives and from official state websites. Statistical analysis was performed using a Chi-Squared test for independence. This analysis determined that the number of canines and felines that tested positive for rabies in each state was correlated to the domestic animal rabies control policy utilized and the terrestrial mammal rabies reservoir in that state. These results suggest that renovation of state rabies prevention and control, and reporting policies as well as additional study would provide a more descriptive analysis of the effectiveness of various rabies control policies as well as provide an opportunity to analyze the breadth and depth of the rabies burden and its impact on human health in the United States.
Keywords: Rabbies; Rabbies control policy; Mammal reservoir; Public Health (0573)